Influence of experience on procedure steps, safety, and functional results in edge to edge mitral valve repair—a single center study. Issue 2 (21st September 2016) - Hamm, Karsten; Zacher, Michael; Hautmann, Martina; Gietzen, Frank; Halbfass, Philipp; Kerber, Sebastian; Diegeler, Anno; Schieffer, Bernhard; Barth, Sebastian
Abstract : Objectives: We sought to determine the effects of experience on the Mitraclip ® procedure steps as well as procedure safety and functional results. Background: MR has proven deleterious in heart failure. Mitraclip ® therapy evolved an important option in patients with severely reduced left ventricular function (LVEF). Methods: Between 2011 and 2016, 126 consecutive patients were grouped in three groups and investigated in a prospective observational study. We evaluated the duration of procedural steps, safety endpoints, and functional results. Results: The median logistic EuroScore was 32% (7–40%). Ninety‐five percent of patients were in NYHA‐stage ≥III and 51% had a LVEF <30%. Groups were homogeneous as to their baseline NYHA status and right heart catheterization data. Echocardiography data are comparable, albeit with a decreasing effective regurgitant orifice area (0.44 ± 0.21 group I vs. 0.34 ± 0.22 group III, P = 0.02). Frailty was less frequent and baseline 6 min walking test results improved from group I to group III. Duration of a first clip placement decreased from 106 ± 50 to 50 ± 21 min ( P < 0.001). Total procedure time decreased from 221 ± 70 to 144 ± 68 ( P < 0.001). The number of clips implanted increased from 66 to 79 ( P = 0.02). MitraClip ® implantation was effective in either group but the combined safety endpoint was reached less frequent in group III ( P = 0.01). There was no difference in MACCE rate, 30 day‐ or intrahospital‐mortality between groups. Conclusion: Safety and duration of procedure steps improved substantially with experience. MR reduction was sustained from the beginning without further improvement. Patient selection is a key factor for success. © 2016 Wiley Periodicals, Inc.